Pelaksanaan Discharge Planning Pada Pasien Postpartum: A Narrative Review - Henny Yulianita; Firman Sugiharto; Risma Dwi Nur Pratiwi; Syifa Fauziah Mutaqin; Alfi Kusuma Dewi; Devi Futri Intan Maria (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: to describe the implementation of discharge planning by nurses in the Maternity Room. Methods: This literature review uses was a narrative review design. The databases used were EbscoHost, Sciencedirect, PubMed, and Google Scholar. The strategy for searching articles using the PCC framework with the keywords “nurse” OR “nursing” OR “health care professional” AND “discharge planning” OR “discharge process” OR “discharge management” AND “postpartum” OR “postnatal” OR “after birth